(untitled) (Economics and region, 2016)
The aspects of evaluation and selection of the investment projects under conditions of uncertainty are considered. The usage of fuzzy set theory for selection of the investment projects is proposed. The advantage of this approach is the ability to project evaluation, taking into account possible changes in key indicators of the project. Also, in addition to using the traditional criterion of the efficiency of the investment project (NPV) is proposed to use such factors as non-financial risks and non-financial benefits. The use of such a model will more clearly define the optimal investment project not only on financial performance, but also taking into account non-financial criteria.